On the Uniform Projection Problem in Descriptive Set Theory - Vladimir Kanovei; Vassily Lyubetsky (Axioms)
For every <semantics>n≥1</semantics>, generic models of <semantics>ZFC</semantics> will be presented for either of the following two sentences: 1. There exists a linear <semantics><msubsup>Σn+21</msubsup></semantics> set not equal to the projection of any uniform planar <semantics><msubsup>Πn+21</msubsup></semantics> set. 2. There exists a linear <semantics><msubsup>Δn+21</msubsup></semantics> set not equal to the projection of any uniform planar <semantics><msubsup>Πn+11</msubsup></semantics> set. Ensuing consistency and independence corollaries are discussed.